2021
DOI: 10.1038/s41366-021-01005-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Roux-en-Y gastric bypass drive changes in miR-31 and miR-215 expression in the human rectal mucosa

Abstract: Background/Objectives Obesity increases colorectal cancer (CRC) risk. However, the effects of weight loss on CRC risk are unclear. Epigenetic mechanisms involving microRNAs that lead to dysregulated gene expression may mediate the effects of obesity and weight loss on CRC risk. We examined the effects of obesity and weight loss following Roux-en-Y gastric bypass (RYGB) on microRNA expression in the human rectal mucosa. Subjects/Methods We collected rectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Differentially expressed miRNAs in obese patients tended to be normalized after bariatric surgery, which was thought to reduce the risk of colorectal cancer. 273 Gastric sleeve surgery can prompt the upregulation of tumor suppressor miR-122 in serum, thus reducing the risk of cancer. 274 In addition, the marked upregulation of lncRNA Gm19619 triggered by a HFD can enhance hepatic gluconeogenesis and lipid accumulation.…”
Section: Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Differentially expressed miRNAs in obese patients tended to be normalized after bariatric surgery, which was thought to reduce the risk of colorectal cancer. 273 Gastric sleeve surgery can prompt the upregulation of tumor suppressor miR-122 in serum, thus reducing the risk of cancer. 274 In addition, the marked upregulation of lncRNA Gm19619 triggered by a HFD can enhance hepatic gluconeogenesis and lipid accumulation.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…This analysis of changes can help identify potential therapeutic targets for T2D. Differentially expressed miRNAs in obese patients tended to be normalized after bariatric surgery, which was thought to reduce the risk of colorectal cancer 273 . Gastric sleeve surgery can prompt the upregulation of tumor suppressor miR‐122 in serum, thus reducing the risk of cancer 274 .…”
Section: Prevention and Treatment Of Obesity‐associated Diseasesmentioning
confidence: 99%
“…A recent study compared the ncRNAs in obese people, colorectal cancer patients, and healthy controls, showing that there is a significant overlap in dysregulated ncRNAs in obese people and cancer patients [ 207 ]. Moreover, another group showed that dysregulated miRs (especially miR-31 and miR-215) are a hallmark of obesity, and that weight loss can change the expression profile of these patients, showing a highly dynamic response of miR expression related to weight [ 208 ]. Leptin is a hormone that is predominantly made by adipose cells and enterocytes in the small intestine; it helps to regulate energy balance by inhibiting hunger, which in turn diminishes fat storage in adipocytes.…”
Section: Effects Of Lifestyle On Ncrna Expression and Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs), a subclass of short non-coding RNAs, mediate post-transcriptional regulation of gene expression. The miRNAs function through pairing with a target messenger RNA inducing different responses according to the level of complementarity, resulting in degradation or translational repression [ 3 , 4 ]. In addition, some miRNAs regulate the translation of proteins, histone modifications and DNA methylation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs packaged within cell-secreted exosomes can modulate local or systemic cell-to-cell communication, and regulate several metabolic pathways [ 3 , 5 , 6 ]. It should be noted that altered miRNA levels are associated with the development of cardiometabolic risk factors [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%